Septuaginta – Prophetische Worte, Textwelten und Versionen - Geiger, Michaela; Ueberschaer, Frank; Meiser, Martin; Fabry, Heinz-Josef (Wissenschaftliche Untersuchungen zum Neuen Testament, 2026)
Prophetic texts of the Old Testament pose special challenges for ancient translators and modern interpreters in terms of textual history and theology. This collected volume brings together studies on the development of textual traditions, translation techniques, and the reception of prophetic texts.